Iconisation and Sociolinguistics of Communication in Nigerian Poetry of English Expression - Arijeniwa, Ademulegun Victor (Randwick International of Education and Linguistics Science Journal, 2024)
This paper's objectives were to: (i) evaluate the iconic presentation of form in Nigerian poetry of English expression; and (ii) identify the textual organization and linguistic elements that serve as communicative signaling in Nigerian poetry. The study determines the implications of poetic discourse on society by using a qualitative research design to generate data and insights from the Peirce model of semiotic theory, specifically with regard to icons. Icons and a few sociolinguistic concepts, like the class variable, served as the foundation for this analysis. This study discovered that: 1. Nigerian poets employ iconic form presentation in their poetry. They can effectively convey their message to the readers by using this device. 2. Together, linguistic components and textual organization serve as articulate devices and communicative signaling, highlighting the expressive significance and implications of Nigerian poetry. The primary focus of literary creation ought to be moral principles. In a time like this, when people desperately need literary works that will change some "maladaptive behavior" in members of society, no work of literature that merely entertains and does not educate the general public can meet the needs of society. Given this, it is advised that poets from Nigeria in particular, as well as literary writers generally, question the moral decay of society and offer solutions. This can be accomplished by presenting the decadence of society in an iconic manner. If applied, social iconization will lead to intellectualism that corrects society's problems.